Empowerment resources, decision-making and gender attitudes: which matter most to livestock keepers in the mixed and livestock-based systems in Ethiopia? - Wole Kinati; Derek Baker; Elizabeth C. Temple; Dina Najjar; Annet Abenakyo Mulema (CABI Agriculture and Bioscience)
Abstract Background Women's empowerment constitutes an important aspect of the development agenda. Although it is highly contextual in nature, empowerment literature so far has focussed on identifying factors associated with empowerment, neglecting the importance of understanding which empowerment resources and agency dimensions are more important for whom and under what contexts. This is important, because we cannot talk of empowerment for those who are not in a disempowered condition or who do not value it. We examine the gender differences in the relative valuations of empowerment resources and decision-making areas across different farming systems, and examine the most valued empowerment resources. Methods Using a mixed methods approach, data on major household decisions, empowerment resources, and their relative importance were collected. Pairwise ranking methods were used to assess their gendered relative importance. Individual interviews using Ryff’s psychological well-being (PWB) items were conducted to obtain quantitative data on the key empowerment resource, which emerged as an important aspect of empowerment from the pairwise ranking exercises. Drawing on the empowerment framework and self-determination theory, we analysed the data. Results Our results show that the major empowerment resources and decision-makings that are valuable to men and women vary across gender and farming systems. In general, men place a greater importance on decisions about livestock, crop and finances. The women valued decisions regarding crop, livestock and social relations. Regarding empowerment resources, psychological well-being was found to be one of the most important resources, for women as well as men. Assessment of the basic psychological needs―autonomy, self-acceptance, and positive relations―statistically yielded no significant differences between the gender groups. However, the effects of location and the intersection of location with gender were both found to be statistically significant, suggesting that being men and from Horo is associated with higher scores on self-acceptance and personal relation subscales. Conclusions We conclude that gender and location play important roles in forming contextual conditions for empowerment and agency implying that empowerment efforts need to consider both. More specifically, policies and intervention efforts to empower individuals or groups must begin by first building their psychological assets and consider contextual gendered perceptions of resources.